1972
DOI: 10.1111/j.1432-1033.1972.tb01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties of a Soluble Catechol O‐Methyltransferase of Human Liver

Abstract: When 2-hydroxyoestradiol-178 was incubated in the presence of S-adenosylmethionine With a 380-fold purified catechol 0-methyltransferase from human liver, 2-methoxyoestradiol-178 and 2-hydroxyoestradiol-178 3-methyl ether were identified as the only metabolites. No dimethylation, transmethylation or demethylation was observed.The purified enzyme was active only in the presence of cysteine and divalent cations; magnesium was found to be the most effective cation. The temperature optimum for the methylation of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…The sensitivity of this FP assay means that it is not necessary to use high AdoMet concentrations that might be needed in other less sensitive assays. In addition, the sensitivity of this assay to low nanomolar concentrations of AdoHcy avoids the problem of product inhibition by AdoHcy known to occur with methyltransferases [40,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of this FP assay means that it is not necessary to use high AdoMet concentrations that might be needed in other less sensitive assays. In addition, the sensitivity of this assay to low nanomolar concentrations of AdoHcy avoids the problem of product inhibition by AdoHcy known to occur with methyltransferases [40,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of this FP assay means that it is not necessary to use high AdoMet concentrations that might be needed in other less sensitive assays. In addition, the sensitivity of this assay to low nanomolar concentrations of AdoHcy avoids the problem of product inhibition by AdoHcy known to occur with methyltransferases [40,[64][65][66].COMT enzyme reactions were performed to test the ability of the FP assay to measure enzyme activity of a methyltransferase. In the FP assay using terminated COMT reactions, FP values decreased proportionally with increasing enzyme concentration and reaction time.…”
mentioning
confidence: 99%
“…Catechol-O-methyltransferase (COMT; EC 2.1.1.6) catalyzes transfer of a methyl group from S-adenosyl-L-methionine (AdoMet) to the hydroxyl group of a variety of catechols, including catecholamine neurotransmitters and the catechol estrogens (23)(24)(25). There are two major COMT isoforms in humans, the soluble cytosolic form (S-COMT) and the membrane-bound endoplasmic reticulum form (MB-COMT) encoded by a single gene at 22q11.2 (26,27).…”
mentioning
confidence: 99%
“…Earlier investigations (3)(4)(5) with mammalian COMT supported the conclusion that the nucleophilic sulfhydryl group of cysteine may be involved in the active site of the enzyme.…”
Section: Ujilmentioning
confidence: 68%
“…Numerous investigations have shown that catechol 0-methyltransferase (S-adenosyl-L-methionine:catechol 0-methyltransferase; catechol methyltransferase; EC 2.1.1.6) (COMT) catalyzes the transfer of the methyl group from S-adenosyl-L-methionine (AdoMet) to one of the vicinal hydroxyl groups of catechols (2), catechol steroids (3,12), catecholamine neurotransmitters (1), xenobiotic catechols (8), and drugs (25) (Fig. 1).…”
mentioning
confidence: 99%